Study of some Pathological Aspects in Sheep Infected with Fasciola gigantica - M.Wahid, F.; I.Altaif, K.; R.Ali, S. (The Iraqi Journal of Veterinary Medicine, 1986)
Little information is available on the pathophysiological changes caused by Fasciola gigantica. The present study aimed at the ellucidation of these changes in Awasi lambs infected with various doses (100, 300 and 600) of metacercariae. The radio-isotop (Fe5%) was used to reveal the ferrokinetic pathway in the blood stream of sheep as a result of infection. All lambs exposed to 100 metacercariae showed the chronic phase of the disease. Of the group exposed to 300 metacercariae, two lambs suffered the subacute phase and the remaining three had the chronic phase. Out of the five lambs given 600 metacercariae, four showed acute syndrom, while the fifth showed the subacute phase of the disease. Blood picture in the acute phase showed severe anaemia of normochronic normocytic type while the anaemia in subacute and chronic phase of th disease was of hypochromic macrocytic type. Using (Fe5%) revealed obvious increase in the amount of iron carried via plasma to the bone marrow, increased plasma iron clearance and rapid incorporation of iron in the newly formed red blood cells. These findings were pronounced in the chronic than in other forms of the disease.